Faktor-Faktor Yang Mempengaruhi Minat Beli Online - Dedi Joko Hermawan (Fakultas Ekonomi Universitas Panca Marga, 2021)
This research has objective to see the interest students of Panca Marga University Probolinggo in online purchasing of goods on a platform shopee, Respondents from the results of this research is customers using shopee platform as a medium purchase of goods online. The sampling technique used non-probability sampling by distributing questionnaires and interviews as a method of collecting data in this study. The data analysis method uses classical assumptions, multiple linear regression, F test and T test. The results show that the level of product quality has a significant influence on buying interest, Advertising variables do not have a significant effect on Buying Interest, The customer trust variable does not have a significant effect on buying interest on the shopee platform. Keywords: Product Quality, Advertising, Customer Trust, Buying Interest